Remote Sensing in Applied Geophysics - Colombero, Chiara; Comina, Cesare; Godio, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue is focused on recent and upcoming advances in the combined application of remote sensing and applied geophysics. Applied geophysics analyzes the distribution of physical properties in the subsurface for a wide range of geological, engineering, and environmental applications at different scales. Seismic, electrical, magnetic, and electromagnetic methods are among the most applied and well-established geophysical techniques. These methods share the advantages of being non-invasive and exploring wide areas of investigation with respect to conventional methods (e.g., drilling). Geophysical surveys are usually carried out deploying or moving the appropriate instrumentation directly on the ground surface. However, recent technological advances have resulting in the development of innovative acquisition systems becoming more typical of the remote sensing community (e.g., airborne surveys). While applied geophysics mainly focuses on the subsurface, typical remote sensing techniques have the ability to accurately image the Earth's surface with high-resolution investigations carried out by means of terrestrial, airborne, or satellite-based platforms. The integration of surface and subsurface information is often crucial for several purposes, including the processing of geophysical data, the characterization and time-lapse monitoring of surface and near-surface targets, and the reconstruction of highly detailed and comprehensive 3D models of the investigated areas. Recent contributions showing the added value of surface reconstruction and/or monitoring in the processing, interpretation, and cross-comparison of geophysical techniques for archaeological, environmental, and engineering studies are collected in this book. Pioneering geophysical acquisitions by means of innovative remote systems are also presented.